ANALISIS KEBUTUHAN APLIKASI UNTUK MENGELOLA STRES AKADEMIK MURID SMKN 2 MAKASSAR - Nur Safitri; Agung Surya Salam; Abid Raisardhi Abdullah; Sinta Nurul Oktaviana Kasim (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
The burden of vocational competencies, the demands of industrial practice, and the anxiety of transitioning into the world of work that trigger psychological stress for students are the background of this research. These operational issues lead to decreased learning concentration and limitations in conventional Guidance and Counseling services that are still reactive. The main focus of this scientific study is to analyze the level of academic stress of students and identify the specific needs for developing a mindfulness-based stress management mobile application at SMKN 2 Makassar. The steps of the development research (R&D) with the ADDIE model are limited to the analysis stage through a mixed-methods explanatory sequential design strategy approach. Sampling was carried out using a purposive sampling method involving 27 twelfth-grade students and 2 counselor teachers as informants. Primary data collection was collected through the Academic Stress Scale, semi-structured interviews, and field observations. Quantitative data empirically revealed that the level of student stress was in the moderate to high category, where as many as 68.96 percent of students often felt anxious due to the burden of assignment evaluations and 75.86 percent of students were worried about their future careers. Students' adaptive coping skills were also minimal, at only around 15 percent. The main conclusion underscores the real urgency of drafting a blueprint for a digital stress management application as an innovative preventive guidance and counseling service.ABSTRAKBeban kompetensi vokasional, tuntutan praktik industri, serta kecemasan transisional menuju dunia kerja yang memicu tekanan psikologis bagi para siswa melatarbelakangi penelitian ini. Masalah operasional tersebut menimbulkan penurunan konsentrasi belajar serta keterbatasan layanan Bimbingan dan Konseling konvensional yang masih bersifat reaktif. Fokus utama kajian ilmiah ini adalah menganalisis tingkat stres akademik siswa serta mengidentifikasi spesifikasi kebutuhan pengembangan aplikasi mobile pengelolaan stres berbasis mindfulness di SMKN 2 Makassar. Langkah-langkah penelitian pengembangan (Research and Development) dengan model ADDIE ini dibatasi pada tahap analisis (analyze) melalui pendekatan mixed-methods strategi explanatory sequential design. Penarikan sampel dijalankan menggunakan metode purposive sampling yang melibatkan 27 siswa kelas dua belas dan 2 guru konselor sebagai informan. Pengumpulan data primer dihimpun lewat Skala Stres Akademik, wawancara semi-terstruktur, dan observasi lapangan. Data kuantitatif secara empiris menyingkap bahwa tingkat stres siswa berada pada kategori sedang hingga tinggi, di mana sebanyak 68,96 persen siswa sering merasa cemas akibat beban evaluasi tugas dan 75,86 persen siswa khawatir terhadap karier masa depan. Kemampuan coping adaptif siswa juga tergolong minim yakni hanya berkisar 15 persen. Simpulan utama menegaskan adanya urgensi nyata terhadap draf cetak biru aplikasi manajemen stres digital sebagai inovasi layanan BK preventif.